Maximising the benefits associated with internship learning for undergraduates - Christine Fanthome (Association for Learning Development in Higher Education (ALDinHE), 2017)
This paper focuses on student responses to an internship programme at an American university in London, with the purpose of highlighting potential areas for curricular improvement. It is based on a survey of 100 undergraduates studying abroad in the UK and concentrates particularly on whether student expectations of their internships are met, the nature of students' perceived personal and professional learning outcomes, and feedback on the current services offered by the internship management team and academic faculty. Findings indicate that student expectations are generally well managed within the current system, and the majority of students feel that their internships have contributed to their personal and professional growth. However, the data highlight discrepancies in the level and nature of support sought by an increasingly diverse student population. Potential improvements are therefore under consideration, such as broader self-help online resources to include video interviews with past students, additional reflective writing workshops, and the establishment of subject linked social media groups for additional peer support.